A book of fragments - Birna Bjarnadóttir 1961- (KIND Publishing, Department of Icelandic Language and Literature, University of Manitoba, 2010)
"This is a collection of poetic fragment ... A text that gradually transformed into a collaborative crush on life ... a journey into some of life's mythic realities, its sorrow and beauty". -- cf. //http://www.mcnallyrobinson.com/9789979707981/birna-bjarnadottir/book-fragments
Keywords: Life in literature; Philosophy in literature